Cooperativism as a Development Model for Philippine Agriculture: Case Study of a Cooperative in Oriental Mindoro - Dela Fuente-Viduya, Alyssa Marie S. (Philippine Journal of Labor and Industrial Relations, 2023)
In examining the role of agriculture cooperativism towards revitalizing the Philippine agriculture, this paper presents the case of a small calamansi (local lemon) farming cooperative, Coop M (not its real name), in Pola, Oriental Mindoro as empirical data. It documents management best practices, feelings of satisfaction of workers, and success stories of individual members. Through interviews, observations, and scrutiny of documents, findings reveal that Coop M complied with most of the cooperative principles and its workers and members were generally satisfied with their cooperative involvement thru non-monetary benefits. Management best practices, satisfaction of workers, and success stories of individual members of Coop M serve as proofs of the huge potential of the said cooperative for sustainability and further success.